Pengaruh employee engagement dan work-life balance terhadap turnover intention di generasi milenial - Lita Chrisdiana; Mukti Rahardjo (Universitas Tarumanagara, 2017)
The purpose of this study was to analyze the influence of employee engagement (X1) and work-life balance (X2) on turnover intention (Y) in millennial generation DKI Jakarta. This research used a non-experimental quantitative design, with nonprobability and snowball sampling techniques. The subject of this study consisted of thirty-one respondents who worked in the Jakarta area, aged between 20 and 36 years old. Data analysis is using multiple linear analyses with additional supported application of SPSS ver. 23. The result obtained from the data analysis showed a significance level of 0,05, employee engagement (t-count = -1,162), which means Ho is accepted, which indicates there is a negative relationship between employee engagement and turnover intention. Moreover, work-life balance (t-count = +2,534), which means Ho is rejected, indicates there is a relationship between variable work-life balance and turnover intention.